Shades of black assembling black arts in 1980s Britain (Duke Univ. Press, 2005)
A history of the last twenty years of Black arts in Britain, focusing on the eighties when, in the midst of social unrest in many cities with large ethnic populations, the Black arts scene exploded into life.